Causal roles and clinical utility of cardiovascular proteins in colorectal cancer risk: a multi-modal study integrating mendelian randomization, expression profiling, and survival analysis - Chenlei Tan; Yanhua Li; Kexin Wang; Ying Lin; Yu Chen; Xuebao Zheng (BMC, 2024)
Abstract Purpose This comprehensive investigation delved into the intricate causal interplay existing between cardiovascular-related plasma proteins and the susceptibility to colorectal cancer, leveraging the robust framework of Mendelian randomization, and employed expression profiling and survival analysis to unravel the latent clinical worth embedded within pertinent gene expressions. Methods Protein quantitative trait loci (pQTLs) of 85 cardiovascular proteins were employed as instrumental variables to investigate the causal relationship between proteins and CRC risk using a Mendelian randomization approach. Causal inferences were graded as strong, intermediate or weak based on statistical checks. Drug-target MR examined VEGF receptors for their potential as therapeutic targets for colorectal cancer. Differential expression analysis, diagnostic ROC curves, and survival analyses were performed for identified proteins using RNA-seq data from The Cancer Genome Atlas (TCGA) colorectal cancer cohort. Results Using cis-pQTLs, LOX-1, VEGF-A and OPG were associated with increased CRC risk (strong evidence), while PTX3, TNF-R2 and MMP-7 were protective (strong evidence). Pan-pQTL analysis found MMP-10 increased risk (intermediate evidence) and ADM increased risk (weak evidence). Drug-target MR found VEGF R1 may be promising therapeutic targets. Differential expression analysis revealed seven genes encoding the identified proteins were dysregulated in tumors. ROC analysis showed five gene expression had high diagnostic accuracy. KM analysis showed four genes had prognostic value. Conclusions This large-scale MR study implicates several cardiovascular proteins in CRC susceptibility and progression. Findings highlight roles for VEGF signaling and extracellular matrix regulation. Results nominate specific proteins as potential diagnostic biomarkers or therapeutic targets warranting further investigation.